Efficacy and Safety of Lenvatinib in Anaplastic Thyroid Carcinoma: A Meta-Analysis - Huang, Dongmei; Zhang, Jinming; Zheng, Xiangqian; Gao, Ming (Frontiers in Endocrinology, 2022)
Background Lenvatinib has shown promising efficacy in targeted therapies that have been tested to treat anaplastic thyroid carcinoma (ATC) in both preclinical and clinical studies. The aim of this study was to evaluate the efficacy and safety of lenvatinib in the treatment of patients with ATC. Methods PubMed, the Cochrane Library, Embase, and ClinicalTrials.gov were searched for potential eligible studies from inception to February 1, 2022. The outcomes included partial response (PR), stable disease (SD), disease control rate (DCR), median progression-free survival (mPFS), and median overall survival (mOS). Effect sizes for all pooled results were presented with 95% CIs with upper and lower limit. Results Ten studies met the inclusion criteria. The aggregated results showed that the pooled PR, SD, and DCR were 15.0%, 42.0%, and 63.0%, respectively. The pooled mPFS and mOS were 3.16 (2.18–5.60) months and 3.16 (2.17–5.64) months, respectively. Furthermore, PFS rate at 3 months (PFSR-3m), PFSR-6m, PFSR-9m, PFSR-12m, and PFSR-15m were 52.0%, 22.5%, 13.9%, 8.4%, and 2.5%, respectively. Meanwhile, the 3-month OS rate (OSR-3m), OSR-6m, OSR-9m, OSR-12m, and OSR-15m were 64.0%, 39.3%, 29.7%, 18.9%, and 14.2%, respectively. The most common adverse events (AEs) of lenvatinib were hypertension (56.6%), proteinuria (32.6%), and fatigue (32%). Conclusions This meta-analysis showed that lenvatinib has meaningful antitumor activity, but limited clinical efficacy in ATC. Systematic Review Registration PROSPERO [https://www.crd.york.ac.uk/PROSPERO/], identifier [CRD42022308624].